The scale epithelium as a novel, non-invasive tool for environmental assessment in fish: Testing exposure to linear alkylbenzene sulfonate - Alves, R. M.S. [UNESP]; Pereira, B. F.; Ribeiro, R. G.L.G.; Pitol, D. L.; Ciamarro, C.M [UNESP]; Valim, J. R.T. [UNESP]; Caetano, F. H. [UNESP] (Elsevier, 2016)
Increasing pollution levels have turned our attention to assessing lethal and sublethal effects of toxic agents using the most informative techniques possible. We must seek non-invasive or non-lethal sampling methods that represent an attractive alternative to traditional techniques of environmental assessment in fish. Detergents are amongst the most common contaminants of water bodies, and LAS (Linear Alkylbenzene Sulfonate) is one of the most used anionic surfactant on the market. Our study analyzed morphological alterations (histological and histochemical) of the scale epithelium of Prochilodus lineatus under exposure to two concentrations of LAS, 3.6 mg/L and 0.36 mg/L, for a period of 30 days and evaluated at 14, 21 and 30 days. In order to establish morphological analysis of the scale epithelium as a new non-lethal environmental assessment tool that is reliable and comparable to classic methods, the relative sensibility of this technique was compared to a commonly used method of environmental assessment in fish, the estimation of the effects of pollutants upon branchial morphology. Two experiments were carried out, testing animals in tanks, and in individual aquariums. Results of analyses on gill tissue show that exposure to 3.6 mg/L of surfactant caused severe damage, including hyperplasia, hypertrophy and fusion at 14 days, with aneurisms at 21 and 30 days; while exposure to 0.36 mg/L had lighter effects on the organ, mainly lower incidence of fusion and hyperplasia. Aditionally, scale morphology was altered severely in response to 3.6 mg/L of LAS, consistently showing increased mucous and club cell production. Epithelial thickness was the most variable parameter measured. Scale epithelium sensibility has the potential to be a reliable environmental marker for fish species since it has the advantage of being less invasive when compared to traditional methods. However, more studies are required to increase the robustness of the technique before it can be generally applied.
Keywords: Gill; LAS; Non-invasive; Prochilodus; Scale; Skin